Efficiency of acupuncture and relaxation sessions in improvement of psychophysical state - Popova, T V; Solar, G; Solarova, Z; Koryukalov, Yu I; Kourova, O G (Voprosy kurortologii, fizioterapii i lečebnoj fizičeskoj kulʹtury, 2020)
A study of the changes in psychophysical function of the human body before and after relaxation sessions and acupuncture application has been conducted. The impact of relaxation sessions on psychophysical performance was studied on a group of university students and postgraduates aged between 18 and 30 years old; the impact of an acupuncture session course - on a group of subjects of a broad age range between 14 and 72, as they underwent rehabilitation therapy for their supportive locomotive apparatus disorders. The recording techniques used included electroencephalography (EEG), psychomotor reaction recording, minute-long time span accuracy reproduction; TST technique (Tactile Solar Test) of meridian and microsystem examination The results of this study suggest that relaxation sessions contribute to the enhancement of neurodynamical performance and mental activity efficiency. After the acupuncture therapy, relaxation effect, and restored tactile sensation on the meridians and microsystems was noted. A conclusion has been made that relaxation sessions and acupuncture may be used to improve psychophysical function.